2014
DOI: 10.1016/j.jtherbio.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the composition of storage and membrane lipids in overwintering larvae of the codling moth, Cydia pomonella

Abstract: The codling moth (Cydia pomonella) is a major insect pest of apples worldwide. It overwinters as a diapausing fifth instar larva. The overwintering is often a critical part of the insect life-cycle in temperate zone. This study brings detailed analysis of seasonal changes in lipid composition and fluidity in overwintering larvae sampled in the field. Fatty acid composition of triacylglycerol (TG) depots in the fat body and relative proportions of phospholipid (PL) molecular species in biological membranes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
(86 reference statements)
0
22
0
Order By: Relevance
“…The FA composition of lipids has been thoroughly analyzed in many insects to understand the dynamic and complex physiological state of diapause (Spike et al, 1991;Ohtsu et al, 1993;Koštál et al, 2003;Basham and Cakmak, 2005;Michaud and Denlinger, 2006;Khani et al, 2007;Koštál, 2010;Rozsypal et al, 2014). The FA composition of triacylglycerols and phospholipids extracted from the whole bodies of non-diapausing and (Fast, 1970;Thompson 1973;Atapour et al, 2007;Khani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The FA composition of lipids has been thoroughly analyzed in many insects to understand the dynamic and complex physiological state of diapause (Spike et al, 1991;Ohtsu et al, 1993;Koštál et al, 2003;Basham and Cakmak, 2005;Michaud and Denlinger, 2006;Khani et al, 2007;Koštál, 2010;Rozsypal et al, 2014). The FA composition of triacylglycerols and phospholipids extracted from the whole bodies of non-diapausing and (Fast, 1970;Thompson 1973;Atapour et al, 2007;Khani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study on O. nubilalis, palmitoleic acid (16:1n-7) comprise a prominent proportion of the total FAs in triacylglycerol and phospholipid FA pools, which is unusual for a Lepidopteran species but more characteristic of Dipteran species (Fast, 1970;Thompson 1973;Buckner et al, 2004). Many authors have found that changes in the FA composition of triacylglycerols and phospholipids are strongly associated with a physiological state of diapause during which many insects develop cold hardiness (Bennet et al, 1997;Kostal and Simek, 1998;Koštál et al, 2003;Buckner et al, 2004;Bashan and Cakmak, 2005;Michaud and Denlinger, 2006;Rozsypal et al, 2014). In O. nubilalis, changes in the FA composition of triacylglycerols and phospholipids led to a significant increase in the overall FA unsaturation (UFAs/SFAs ratio) during transition and time course of diapause, which significantly decreased during the termination period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both E. solidaginis and E. scudderiana have more unsaturated lipids in winter than in summer (Joanisse and Storey, 1996) and, as a consequence of this, E. solidaginis has lipid droplets that remain sufficiently liquid to coalesce when the cytoplasm of the cell freezes (Salt, 1959;Lee et al, 1993). Similarly, the proportion of polyunsaturated (18:2) fatty acids in the storage lipids of codling moth (Cydia pomonella) larvae increases during winter, with a consequent 5-10°C decrease in the melting point of the storage lipids (Rozsypal et al, 2015). Although vertebrates generally cannot synthesise polyunsaturated fatty acids (PUFAs), or desaturate monounsaturated fatty acids to generate PUFAs, several groups of insects (notably excluding Drosophila) appear able to do so (de Renobales et al, 1987;Stanley-Samuelson et al, 1988).…”
Section: Using Fats At Subzero Body Temperaturesmentioning
confidence: 99%